The Impact Of Ai-Assisted Digital Pedagogy On Efl Students Speaking Self-Efficacy - Kamarudin, Kamarudin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of information and communication technology in recent years has driven the transformation of English as a Foreign Language (EFL) learning, particularly through the application of digital pedagogy. One of the latest innovations in digital pedagogy is the use of artificial intelligence (AI), which enables learning to be more personalized, adaptive, and less stressful. However, empirical studies that specifically examine the impact of AI-assisted digital pedagogy on the speaking self-efficacy of EFL students in higher education contexts are still limited. This study aims to examine the impact of AI-assisted digital pedagogy on the speaking self-efficacy of EFL students in the English Education Study Program, Faculty of Culture, Management, and Business, Mandalika University of Education. This study uses a quantitative approach with a one-group pre-test and post-test pre-experimental design. The research subjects consisted of 30 EFL students selected using purposive sampling. Data were collected through a speaking self-efficacy questionnaire adapted from Bandura's self-efficacy theory, then analyzed using descriptive statistics and a paired sample t-test. The results showed an increase in students' speaking self-efficacy after the implementation of AI-assisted digital pedagogy. The average speaking self-efficacy score increased from 68.40 on the pre-test to 82.73 on the post-test. The paired sample t-test results showed a significant difference between the pre-test and post-test scores (t = 7.214; p < 0.05). In addition, there was a shift in students' self-efficacy levels from the low and moderate categories to the high category. Based on these findings, it can be concluded that AI-assisted digital pedagogy has a positive and significant impact on improving the speaking self-efficacy of EFL students. The integration of AI in the learning is not only supports the development of speaking skills but also strengthens the affective aspects of students, particularly self-confidence, which plays an important role in successful oral communication